Perceived Diversity, Inclusive Leadership, and Discrimination: The Mediating Role of Inclusion on Employee Well-Being - Syauqi Pinandito; Muafi Muafi (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study examines how perceived diversity, inclusive leadership, and discrimination impact employee well-being, with employee inclusion as a mediator. It highlights the importance of inclusive leadership and the absence of discrimination for positive workplace outcomes and addresses the limited research on these relationships in Indonesia. Research Methodology: This study employed a quantitative survey design. Data were collected from 206 permanent employees of PT XYZ Bekasi using purposive sampling. The data were analyzed using structural equation modeling partial least squares (SEM-PLS) with SmartPLS 4 to assess both direct and indirect relationships among the variables. Results: Perceived diversity does not significantly affect employee inclusion. Inclusive leadership positively impacts both inclusion and well-being, while discrimination negatively affects inclusion. Employee inclusion positively influences well-being and mediates the effects of leadership and discrimination on well-being, but not the effect of perceived diversity. Conclusions: Employee inclusion plays a crucial role in enhancing employee well-being, particularly through inclusive leadership practices and discrimination reduction. Perceived diversity alone is insufficient to foster inclusion or well-being without supportive organizational practices. Limitations: This study was limited to a single organization and employed a cross-sectional design, which may restrict the generalizability and causal interpretation of the findings. Contributions: This study contributes to the literature by highlighting employee inclusion as a key psychological mechanism linking inclusive leadership and discrimination to employee well-being in diverse organizational settings in Indonesia.